2015
DOI: 10.4236/psych.2015.613163
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Attitudes toward Surveillance at Work and Its Correlates

Abstract: A large British sample completed measures of job autonomy and satisfaction as well as work discrimination and attitudes to authority measures along with a new surveillance at work measure. The new 16 item surveillance at work measure factored into two clear factors which reflected positive and negative attitudes to surveillance. Higher scores on Negative Aspects of Surveillance were significantly associated with lower job satisfaction, lower job autonomy, greater perceived discrimination at work, more negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The study showed, similar to Furnham and Swami's (2015) Interestingly, the items which attracted most agreement were 19 (I probably could not tell if I were under surveillance), 7 (Surveillance systems are necessary because they help in the identification and apprehension of criminals) and 1 (Surveillance systems help protect society from terrorists and criminals) while those that attracted most disagreement was 16 (I sometimes feel as though I am constantly being watched or monitored by surveillance), 25 (Surveillance does or would motivate me to be a better citizen) and 18 (Surveillance alienates people because it makes the more likely to self-police each other).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The study showed, similar to Furnham and Swami's (2015) Interestingly, the items which attracted most agreement were 19 (I probably could not tell if I were under surveillance), 7 (Surveillance systems are necessary because they help in the identification and apprehension of criminals) and 1 (Surveillance systems help protect society from terrorists and criminals) while those that attracted most disagreement was 16 (I sometimes feel as though I am constantly being watched or monitored by surveillance), 25 (Surveillance does or would motivate me to be a better citizen) and 18 (Surveillance alienates people because it makes the more likely to self-police each other).…”
Section: Discussionsupporting
confidence: 74%
“…Similar scale dimensionality on surveillance related topics has been reported by Furnham and Swami (2015). It is quite probable that the factor structure was affected by the positive and negative wording of the items (Schmitt & Stults, 1985).…”
Section: Surveillance Attitudes Questionnaire Exploratory and Confirmsupporting
confidence: 72%
See 2 more Smart Citations
“…Many employees may not read or fully understand these documents and click to accept without comprehending their implications. Few people have considered the ethics of these techniques and employee attitudes to surveillance (Furnham & Swami, 2015).…”
Section: Wearable Technologymentioning
confidence: 99%